Anxiety, depression and coping styles in mothers of children with cow's milk protein allergy - Tanir, Yasar; Asik, Abdulvahit (Annals of Medical Research, 2023)
Aim: Cow’s milk protein allergy (CMPA) in the infant is shown to be associated with heightened anxiety in the parents. However, depression and coping styles were not studied in parents of children with CMPA. The object of this study was to investigate the internalizing problems and coping styles in mothers of youngsters with CMPA.Materials and Methods: The sample contained 41 subjects with CMPA and 41 subject without any chronic health problems, aged between 4 and 11 months. Anxiety, depression and coping styles of mothers were measured with Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and Coping Attitudes Rating Scale (COPE).Results: There were significant differences between the two groups in terms of anxiety and depression levels (p< 0.001). The mothers in the CMPA group used active emotional coping strategies less than control group (p=0.021). Total breastfeeding duration of the children in the CMPA group was lower than the healthy controls (p=0.008). There was negative correlation between active emotional coping scores and the time of adding supplemental food to infant’s diet (r=-0.42, p=0.06). Children who had additional food allergies breastfed less than the children who had only CMPA (p=0.02).Conclusion: Mothers of the children with CMPA are under heightened risk for anxiety and depression. Children with CMPA may be at risk for shorter duration of breastfeeding. Anxious and depressed caregivers may be referred for psychological help since the first year of life is essential for healthy psychological development of the children.
Keywords: Anxiety; Depression; Coping styles; Mother; Cow's milk protein allergy